Response to Beth Richie's “Black Feminism, Gender Violence and the Build-up of a Prison Nation” - Kimberly D. Bailey (Washington University Journal of Law & Policy, 2011)
With respect to the violence against women movement, Professor Richie has always been a voice for those women who generally do not have a voice, specifically poor women, women of color, and immigrant women. Her insight today that the mainstream feminist theorization of domestic violence continues to leave them voiceless is a particularly important one. I would like to continue her conversation by focusing on the concept of privacy. I use this term in the same sense that liberal theorists use it, as a representation of a sphere that is inappropriate for government intrusion. As other scholars have noted, this concept has been somewhat complicated in the context of women’s rights. On the one hand, the concept of decisional privacy—or what some prefer to call liberty—is the foundation for such rights as contraceptive use and abortion. On the other hand, privacy historically was also used to justify inaction on the part of the police, judges, and prosecutors in response to women who would seek intervention from the criminal justice system in order to stop the violence that they were experiencing in their homes. In other words, the privacy of the patriarchal head of the household to run his home as he saw fit was valued over the bodily integrity of the wife.
Keywords: Black womanhood; Domestic violence; Poor women; Right of privacy; United States